Penyuluhan dan Aksi Bersih Sungai untuk Mengurangi Pencemaran Air dan Meningkatkan Kepedulian Lingkungan - Sihasale, Daniel Anthoni; Pinoa, Wiclif Sephnath; Lasaiba, Mohammad Amin (Universitas Pattimura, 2024)
This river cleanup and counseling activity aimed to reduce water pollution and enhance environmental awareness within the community. The counseling sessions were designed to improve the community's understanding of water pollution's impact and emphasize the importance of maintaining river cleanliness. The cleanup effort involved the active participation of community volunteers and local government in removing pollutants from the river. This initiative is expected to foster behavioral changes in waste management and environmental stewardship, resulting in sustainable improvements in water quality. Additionally, this activity is a foundational step towards fostering long-term collaboration between the government, local communities, and environmental organizations for maintaining clean water and promoting ecological sustainability.